Function and Its Application in Real Life - Chaudhary, Parshuram (Haimaprabha, 2025)
The study presents ordered pairs, relations, and functions, examining their theoretical and practical applications. This study intends to implement fundamental mathematical concepts in practical scenarios. Examples and problem-solving methods were employed to examine functions and their real-world applications. Sequential instructional resources illustrate the observation of real-world functions. Secondary data was gathered from academic journals, research reports, and textbooks to support and explain these applications. The study advocates for problem-solving utilizing ordered pairs, relations, and functions following a literature and mathematical review. The study also addresses methods for instructing college students and researchers in these principles. The findings indicate that ordered pairs, relation, and functions facilitate the resolution of intricate global issues. The examination of water usage, academic schedules, and rice preparation illustrates the significance of essential functions. This study suggests that comprehending these concepts enhances everyday problem-solving and decision-making. Utilizing functions in everyday life improves mathematical understanding and application. The study indicated that acknowledging the significance of functions in real-world contexts enhances education and decision-making. The research seeks to promote comprehension and application of functions beyond basic mathematical principles. This study emphasizes that comprehending mathematical functions improves the capacity to model, analyze, and resolve real-life daily activities, particularly in educational contexts, water consumption, and rice preparation.